THE EFFECT OF PROCESS CONDITIONS IN PREPARATION OF VEGETABLE BROTH AS SAVORY FLAVOR FROM MUNG BEANS (Phaseolus radiatus L.) USING INOCULUM OF Rhizopus-C1 - Agustine Susilowati; Aspiyanto Aspiyanto; Hakiki Melanie; Yati Maryati (Indonesian Journal of Chemistry, 2008)
Preparation of vegetable broth from mung beans (Phaseolus radiatus L.) in semi pilot scale is an attempt development to get product of savory flavor in larger scale. The aim of this activity was to find out the effect of process multiplication on composition of vegetable broth from mung beans using inoculum of Rhizopus-C1 through brine fermentation in mixtures of inoculum, salt, and mung beans of 26, 23, and 51 %. This activity was conducted in both temperature of fermentation (room temperature and 30 °C), various time of fermentation (0, 2, 4, 6, 8, 10, and 12 weeks) and process scales, namely laboratory scale (300 g) and semi pilot scale (± 25 kg), respectively. The result of experiment indicated that fermentation temperature and time and process scales were tend to affect on composition of product. The length of fermentation time would increase concentrations of dissolved protein, N-amino and reducing sugar, decreased concentrations of fat and Volatile Reduction Substance (VRS), while concentrations of total protein, and water were tend to be constant in laboratory and semi pilot scales at the both process temperatures. Multiplication in preparation process of inoculum (7 kg) using starter of Rhizopus-C1 resulted inoculum with activities of proteolytic of 0.71 U/g, and amilolytic of 17.5 U/g at 56 h of incubation. The whole process in semi pilot scale decreased composition of products. The optimal treatment based on recovery of total protein, and the highest amino acids as N-amino in semi pilot scale was at fermentation temperature of 30 ºC for 10 weeks with concentrations of water of 44.96%, total protein of 11.77% (dry matter), dissolved protein of 8 mg/mL, N-amino of 15.4 mg/mL, reducing sugar of 582.5 mg/mL, fat of 0.26% and, VRS of 90 µeq.reduction/g.